Isatuximab, carfilzomib, and dexamethasone in patients with relapsed multiple myeloma: updated results from IKEMA, a randomized Phase 3 study - Martin, Thomas; Dimopoulos, Meletios-Athanasios; Mikhael, Joseph; Yong, Kwee; Capra, Marcelo; Facon, Thierry; Hajek, Roman; Špička, Ivan; Baker, Ross; Kim, Kihyun; Martinez, Gracia; Min, Chang-Ki; et al. (Blood cancer journal, 2023)
Longer-term outcomes with the anti-CD38 antibody isatuximab in combination with carfilzomib-dexamethasone (Isa-Kd) were evaluated in the randomized Phase 3 trial IKEMA (NCT03275285), in a prespecified, follow-up analysis of progression-free survival (PFS, primary study endpoint), final complete response (CR) using Hydrashift Isa immunofixation assay, minimal residual disease (MRD) negativity, and safety. Enrolled patients had relapsed/refractory multiple myeloma (1-3 prior treatment lines). Isa 10 mg/kg was administered intravenously weekly in cycle 1 then biweekly. Efficacy analyses were performed in the intent-to-treat population (Isa-Kd: n = 179, Kd: n = 123) and safety evaluated in treated patients (Isa-Kd: n = 177, Kd: n = 122). Consistent with the primary interim analysis, the addition of Isa to Kd prolonged PFS (HR 0.58, 95.4% CI: 0.42-0.79; median PFS 35.7 [95% CI: 25.8-44.0] vs 19.2 [95% CI: 15.8-25.0] months). PFS benefit was observed with Isa-Kd across subgroups, including patients with poor prognosis. The stringent CR/CR rate was 44.1% vs 28.5% (odds-ratio: 2.09, 95% CI: 1.26-3.48), the MRD negativity rate 33.5% vs 15.4% (odds-ratio: 2.78, 95% CI: 1.55-4.99) and the MRD negativity CR rate 26.3% vs 12.2%, with Isa-Kd vs Kd. The safety profile of Isa-Kd was similar to that reported in the prior interim analysis. These findings further support Isa-Kd as a standard-of-care treatment for relapsed multiple myeloma patients.Clinical trial information: ClinicalTrials.gov, NCT03275285.
Keywords: Multiple Myeloma; mnohočetný myelom; dexamethason; protokoly protinádorové kombinované chemoterapie; Antibodies, Monoclonal, Humanized; Humans; lidé; humanizované monoklonální protilátky; Dexamethasone; Antineoplastic Combined Chemotherapy Protocols